Study on morphological characteristics of the ladybird beetles (Coleoptera: Coccinellidae) and their host-plants posibility in Joensuu, Finland - Rahaman, SK. M.; T., Aniszewski (Malaysian Society of Applied Biology, 2016)
The survey of the ladybird beetles population was conducted in Joensuu area, Finland, over a period of three years from mid- May 2010 to mid-August 2013. All the specimens of the coccinellid ladybird beetles were collected from five major localities: City centre, Linnunlahti, Karsikko, Utra and Pilkko areas. In the family Coccinellidae, 16 species belonging to 10 genera were found in our experiment time. Most of ladybird’s common host–plant was Rosa rugosa and also other different species of plants. All the host-plants were growing naturally in the local ecosystem of the experimental area. Out of the 16 species of ladybird beetles from Joensuu, there were two species (Cryptolaemus montrouzieri and Chilocorus stigma) reported for the first time from North Karelia and is therefore, a new addition to the ladybird beetles fauna of Finland.